Reader's Digest : Select Editions : The Woods, Written in Bone, White City, Thunder Bay - Coben, Harlan, 1962- [et al.] (London Reader's Digest, 2007)
As a dedicated lawyer, Paul Copeland is having a difficult time in court, defending a young woman who says two university students raped her. What if Copeland is hiding something in his past that will force him to drop the charges? Indeed his teenage sister went missing twenty years ago. Her body was never found in the woods where she disapeared that night. Copeland was not where he shoud have been either. [Source : 4e de couv.]
Include Illustration
Keywords: Public prosecutors -- New Jersey -- Missing children